2022
DOI: 10.3389/fmicb.2022.969524
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gut microbiota improve SCFA production and fiber utilization in Tibetan pigs fed alfalfa diet

Abstract: Tibetan pigs were thought to have good performances of rough feeding tolerance, which may be related to the gut microbiota. This study was conducted to investigate the changes of colonic microbiota contribute to fiber utilization in Tibetan pigs fed alfalfa supplementation diet compared with basal diet, and verified whether the microbial community in Tibetan pigs fed alfalfa diet was beneficial to utilize fiber using in vitro fermentation. A total of 40 Tibetan pigs were allocated into two groups and fed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Lachnospiraceae_NK3A20_group is a butyrate-producing bacterium that is beneficial to intestinal health and has also been found to be significantly negatively correlated with residual feed intake in animals, closely related to linoleic acid metabolism and lysine degradation in ruminants and able to improve metabolic levels in animals [ 52 ]. Rikenellaceae_RC9_gut_group and Lachnospiraceae_UCG-010 , which appear to be upregulated in the HMet group, are also considered to facilitate the utilization of crude fiber feed and the production of SCFA in animals [ 53 , 54 ]. These results suggested that changes in fecal microbial response to methionine supplementation were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae_NK3A20_group is a butyrate-producing bacterium that is beneficial to intestinal health and has also been found to be significantly negatively correlated with residual feed intake in animals, closely related to linoleic acid metabolism and lysine degradation in ruminants and able to improve metabolic levels in animals [ 52 ]. Rikenellaceae_RC9_gut_group and Lachnospiraceae_UCG-010 , which appear to be upregulated in the HMet group, are also considered to facilitate the utilization of crude fiber feed and the production of SCFA in animals [ 53 , 54 ]. These results suggested that changes in fecal microbial response to methionine supplementation were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Blautia has been shown to modulate host health and attenuate metabolic syndrome ( Liu et al, 2021 ). Marvinbryantia facilitates fiber breakdown, aids in the digestion of the cecum and replenishes energy ( Gao et al, 2022 ). Related studies have reported that both Tyzzerella-3 and Marvinbryantia are associated with the synthesis of SCFA (Short Chain Fatty Acids), and their elevated abundance implies an increase in the ability to maintain the intestinal barrier ( Zhang et al, 2020 ; Gao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marvinbryantia facilitates fiber breakdown, aids in the digestion of the cecum and replenishes energy ( Gao et al, 2022 ). Related studies have reported that both Tyzzerella-3 and Marvinbryantia are associated with the synthesis of SCFA (Short Chain Fatty Acids), and their elevated abundance implies an increase in the ability to maintain the intestinal barrier ( Zhang et al, 2020 ; Gao et al, 2022 ). The potential pathogens Desulfovibrio and Alistipes , the diarrhea causative agent Escherichia-Shigella ( Nataro and Kaper, 1998 ), were significantly higher in relative abundance in summer than in the other two seasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, Clostridium sensu stricto 1 , Proteus , and Gemella have been proven to have a role in accelerating the occurrence of IBD ( Lopez-Dupla et al., 1996 ; FitzGerald et al., 2006 ; Garrett et al., 2010 ; Wen et al., 2021 ). Inclusively, Marvinbryantia , Rikenellaceae RC9 gut group , Akkermansia , Alloprevotella , Odoribacter , and Clostridia UCG 014 were all potential beneficial bacteria that could promote the synthesis of short-chain fatty acids (SCFAs) with the function of inhibiting the expression of inflammatory factors ( Gao et al., 2022 ; Hu, 2022 ; Leibovitzh et al., 2022 ; Cai et al., 2023 ; Gao et al., 2023 ; Han et al., 2023 ). Therefore, the dramatic changes in Escherichia-Shigella and Muribaculaceae relative abundance might be one of the main reasons for deterioration and death from days 36 to 45.…”
Section: Discussionmentioning
confidence: 99%